Managing natural forests for sustainable harvests of mahogany (Swietenia macrophylla): experiences in Mexico's community forests - Snook, Laura K.; Santos Jimenez, M.; Carreon Mundo, M.; Chan Rivas, C.; May Ek, F.J.; Mas Kantun, P.; Nolasco Morales, A.; Hernández Hernández, C.; Escobar Ruiz, C. (2003)
In 2002, mahogany (Swietenia macrophylla) was listed on Appendix II of CITES (the Convention on International Trade in Endangered Species). This requires that all producing countries define and implement sustainable production systems for mahogany, the most commercially important neotropical timber, which is still harvested from natural forests. The only serious efforts to produce mahogany sustainably from managed natural forests are those of communities in Quintana Roo, Mexico, which control 800,000 of natural production forests. Thirty-six of them currently produce a total of 7,000 m3/yr of mahogany timber. For the past 20 years, foresters and researchers have been testing and developing management systems to ensure sustainable harvests of mahogany. This has been challenging, because mahogany is typically selectively logged from a matrix of more abundant, noncommercial species, leaving a closed forest canopy and too much shade for the survival of mahogany seedlings. Researchers collaborating with communities and their foresters have carried out a range of experiments to determine how to ensure the regeneration of mahogany on community production forests. This article synthesizes twenty years of progress towards sustainable forest management on the part of the forest communities of Quintana Roo, and recent insights from 7 years of research on mahogany seed production and the establishment, survival and growth of mahogany seedlings from natural regeneration, sown seed, and planted seedlings, in response to different kinds of silvicultural treatment in natural forests.